The association between proton pump inhibitor use and the risk of adverse kidney outcomes: A systematic review and meta-Analysis - Surapon Nochaiwong (2018)
© 2017 The Author . Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved. Background Existing epidemiological studies illustrate that proton pump inhibitors (PPIs) may be related to adverse kidney outcomes. To date, no comprehensive meta-Analysis has been conducted to evaluate and quantify this association. Methods We performed a systematic review and meta-Analysis of studies to assess the association between PPI use and the risk of adverse kidney outcomes. We searched MEDLINE, Embase, SCOPUS, Web of Science, CINAHL, Cochrane Library and grey literature with no language restrictions (through 31 October 2016). Adverse kidney outcomes were acute interstitial nephritis (AIN), acute kidney injury (AKI), chronic kidney disease (CKD) and end-stage renal disease (ESRD). The risk ratios (RRs) and confidence intervals (CIs) were pooled using a random effects model. The strength of evidence (SOE) for each outcome was assessed using the Grading of Recommended Assessment, Development and Evaluation system. Results Of 2037 identified studies, four cohort and five case-control studies with â 1/42.6 million patients were included. Of these, 534 003 (20.2%) were PPI users. Compared with non-PPI users, PPI users experienced a significantly higher risk of AKI [RR 1.44 (95% CI 1.08-1.91); P = 0.013; SOE, low] and CKD [RR 1.36 (95% CI 1.07-1.72); P = 0.012; SOE, low]. Moreover, PPIs increased the risk of AIN [RR 3.61 (95% CI 2.37-5.51); P < 0.001; SOE, insufficient] and ESRD [RR 1.42 (95% CI 1.28-1.58); P < 0.001; SOE, insufficient]. Conclusion PPI usage was associated with adverse kidney outcomes; however, these findings were based on observational studies and low-quality evidence. Additional rigorous studies are needed for further clarification.